Measuring R&D effectiveness-I Robert Szakonyi offers an approach based on how well an R&D department performs ten key activities - Szakonyi, Robert (Research management (Now: research technology management))
How well an R&D department performs ten basic activities indicates its effectiveness-and how it can improve.